Σ-Holes promote the concertedness in nucleophilic aromatic substitution reactions of nitroarenes1. (8th May 2019) - Gallardo-Fuentes, Sebastián; Ormazábal-Toledo, Rodrigo
Abstract : Concertedness in SNAr may be modulated by the presence of a σ-hole. Abstract : The mechanism of the SNAr reactions between 1-halo-2, 4-dinitrobenzenes and amines was revisited by means of DFT calculations. Remarkably and contrary to the traditional text-book perspective, the dehalogenation of 1-X-2, 4-dinitrobenzenes bearing good leaving groups (X = Cl, Br and I) by soft nucleophiles involves a single-step mechanism passing through a barrierless C–X bond cleavage step. Solely the reaction of 1-fluoro-2, 4-dinitrobenzene follows the traditional addition–elimination pathway. The analysis of the charge transfer patterns along the reaction path for the whole systems studied suggests that for those nitroarenes exhibiting σ-holes the dehalogenation mechanism occurs through a single-step. Nucleophile effects on the reaction rates were also discussed.